An Audit On Waiting Period For Alveolar Bone Graft (ABG) After Pre-ABG Orthodontic Treatment In Abdul Samad Orthodontic Clinic - A/P Nathan, Nivethiny (IIUM Medical Journal Malaysia, 2017)
Introduction: The timing of ABG procedure in a cleft patient is crucial to provide room and bony support for the eruption of canine. However, there seems to be a delay in execution of this procedure in certain centres. Material and Methods: Sample consists of records of cleft patients treated from 2000-2016. The date and age for commencement of active orthodontic treatment, date referred for ABG and date ABG done were retrieved. The centres that conducted these surgeries identified. Results: The mean age at start of treatment was 11.03 for males and 11.47 for females. Average waiting period for ABG was 11.75 months with the shortest was 12 days and the longest was 35 months. Conclusion(s): Delay in ABG increase the risks associated with prolonged wear of fixed orthodontics. Distribution of burden of care among the surgical centres to reduce this waiting time should be taken into consideration for the benefit of patients.